2002
DOI: 10.1128/mcb.22.8.2642-2649.2002
|View full text |Cite
|
Sign up to set email alerts
|

New Insights into the Pleiotropic Drug Resistance Network from Genome-Wide Characterization of the YRR1 Transcription Factor Regulation System

Abstract: Yrr1p is a recently described Zn 2 Cys 6 transcription factor involved in the pleiotropic drug resistance (PDR) phenomenon. It is controlled in a Pdr1p-dependent manner and is autoregulated. We describe here a new genome-wide approach to characterization of the set of genes directly regulated by Yrr1p. We found that the time-course production of an artificial chimera protein containing the DNA-binding domain of Yrr1p activated the 15 genes that are also up-regulated by a gain-of-function mutant of Yrr1p. Gel m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
93
0
3

Year Published

2004
2004
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 99 publications
(99 citation statements)
references
References 27 publications
3
93
0
3
Order By: Relevance
“…This is the case with CIN5, also named YAP4, whose function is not clear and which was already shown to be induced under conditions of either oxidative or osmotic stress (see reference 25 for a review). YRR1, which codes for a zinc finger transcription (7,19), is also activated by benomyl, probably via the activation of Yap1. The presence of Yap1 recognition elements in the promoters of both CIN5/YAP4 and YRR1 suggests a direct interaction of Yap1 with these promoters.…”
Section: Resultsmentioning
confidence: 99%
“…This is the case with CIN5, also named YAP4, whose function is not clear and which was already shown to be induced under conditions of either oxidative or osmotic stress (see reference 25 for a review). YRR1, which codes for a zinc finger transcription (7,19), is also activated by benomyl, probably via the activation of Yap1. The presence of Yap1 recognition elements in the promoters of both CIN5/YAP4 and YRR1 suggests a direct interaction of Yap1 with these promoters.…”
Section: Resultsmentioning
confidence: 99%
“…In S. cerevisiae, pleiotropic drug resistance is not solely mediated by Pdr3 but may involve other regulators, viz. Pdr1, Pdr8, Yrr1 and its paralogue Yrm1 (DeRisi et al, 2000;Le Crom et al, 2002;Hikkel et al, 2003;Onda et al, 2004;Lucau-Danila et al, 2005). This response Transcriptional profiling of carotenoid-producing S. cerevisiae 991 C E N .…”
Section: Carotenoid Production Induces Expression Of Genes Involved Imentioning
confidence: 98%
“…We reasoned that carotenoids, which are hydrophobic compounds (Gruszecki and Strzalka, 2005), cannot readily dissolve in the media used for the growth of yeast strains but are more likely to remain attached to cellular membranes. To determine whether carotenoids could be secreted from Orange02 cells during growth in batch cultures, 20% v/v sunflower oil, which is a proper solvent * * * 0 (DeRisi et al, 2000;Le Crom et al, 2002;Devaux et al, 2002;Hikkel et al, 2003;Tuttle et al, 2003;Lucau-Danila et al, 2003;Onda et al, 2004 Nawrocki et al, 2001;Hikkel et al, 2003;Tuttle et al, 2003;Onda et al, 2004) PDR15 2 (Wolfger et al, 1997;DeRisi et al, 2000;Hikkel et al, 2003;Tuttle et al, 2003) YLR346C 3 (DeRisi et al, 2000;do Valle Matta et al, 2001;Le Crom et al, 2002;Devaux et al, 2002;Hikkel et al, 2003;Tuttle et al, 2003;Onda et al, 2004) PDR5 6 (DeRisi et al, 2000Miura et al, 2001;Devaux et al, 2002;Teixeira and Sa-Correia, 2002;Tuttle et al, 2003;Lucau-Danila et al, 2003;Onda et al, 2004;Wehrschutz-Sigl et al, 2004 DeRisi et al, 2000;Le Crom et al, 2002;Devaux et al, 2002;Hikkel et al, 2003;Tuttle et al, 2003;Lucau-Danila et al, 2003;Onda et al, 2...…”
Section: Carotenoid Secretion From Carotenoid-producing S Cerevisiaementioning
confidence: 99%
“…These transcription factors have in common a Zn(2)-Cys(6) DNA-binding domain which targets sequences with direct, inverted, or everted palindromic repeats containing a 5Ј-CGG-3Ј motif with various numbers of nucleotides in the intervening spacer region. Several examples can be cited from studies performed with S. cerevisiae: Hap1p recognizes the direct repeat 5Ј-CGGNNNTANCGG-3Ј; the heterodimer Pip2p/Oaf1p binds to inverted repeats of the consensus sequence 5Ј-CGGN 15-18 -CCG-3Ј; Pdr8p and Yrr1p, which are factors involved in multidrug resistance, target DNA-binding motifs containing the 5Ј-CGG-3Ј triplet in dyad symmetry; and Pdr1p and Pdr3p regulate their targets via the everted sequence motif 5Ј-TCCG/aC/tGG/cA/g-3Ј (where lowercase letters indicate variable bases in a consensus motif) (9,17,23). More recently, it was shown that War1p binds the cis-acting element 5Ј-CGG-N 23 -CCG-3Ј, which is essential for PDR12 activation and resistance to weak acid stress (22).…”
Section: Discussionmentioning
confidence: 99%